Analisis Yuridis Terhadap Putusan Hakim Yang Menjatuhkan Pidana Kurungan Terhadap Pembawa Senjata Tajam Oleh Anak - Teni Oktapriani; Marsanuddin Marsanuddin; Muhammad Lutfi (Universitas Sang Bumi Ruwa Jurai, 2018)
Therefore this study aims to find out what is the legal basis of judges 'consideration in imposing criminal sanctions for carrying weapons of sharp weapons by children and to find out how the judges' decisions against criminal sanctions carried out by children in criminal cases Number 79 / Pid.Sus-Anak / 2017 /PN.Tjk.The method used in this study is descriptive normative. The procedure of data collection is done by means of library research and field studies. This research was carried out in the Tanjung Karang District Court, in order to achieve this goal the author used data collection techniques in the form of library research and field research by conducting direct interviews with judges at the Tanjung Karang District Court.The results of this study conclude that: (1) the basis for consideration of judges who impose criminal sanctions on children who carry sharp weapons in the application of criminal law (Number 79 / Pid.Sus-Anak / 2017 / PN.Tjk) is in accordance with the provisions stipulated in Article 2 Paragraph (1) of Law Number 12 of 1951. (2) Implementation of a judge's decision on a sentence of imprisonment committed by a child, in deciding a case the judge has considerable considerations, starting from the demands of the public prosecutor, witness statements, statement of the defendant, and evidence, as stipulated in article 197 of the Criminal Procedure Code, and the fulfillment of elements in accordance with the indictment as well as the laws of the child and there is no justification, so that they are found guilty, as well as things that are burdensome and mitigating. The panel of judges had many considerations so that the defendant had to account for his actions in accordance with the verdict handed down by the judge by serving a sentence of imprisonment for 2 months in prison and paying court fees of IDR 2000 rupiah.